2022
DOI: 10.1109/access.2022.3142817
|View full text |Cite
|
Sign up to set email alerts
|

Beans Leaf Diseases Classification Using MobileNet Models

Abstract: In recent years, plant leaf diseases has become a widespread problem for which an accurate research and rapid application of deep learning in plant disease classification is required. Beans is also one of the most important plants and seeds which are used worldwide for cooking in either dried or fresh form. Beans are a great source of protein that offer many health benefits, but there are a lot of diseases associated with beans leaf which hinder its production such as angular leaf spot disease and bean rust di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(33 citation statements)
references
References 18 publications
0
23
0
1
Order By: Relevance
“…This accuracy is improved due to use of BFO process, which assists in identification of high-density feature sets, that have lower redundancies. Similarly, the precision levels for crop disease identification can be observed from table 3 MNet [8] SPED CNN [6] As per this extensive evaluation and its visualization in figure 4, it can be observed that the proposed model is able to improve classification precision levels by 18.3% when compared in SPED CNN [6], 9.4% when compared with MNet [8], and 8.5% when compared with FR CNN [9], which makes it highly useful for an extensive set of consistencyaware classification scenarios. This precision is improved due to use of ensemble classification process, which assists in identification of optimal classes for different disease types.…”
Section: Results Evaluation and Comparative Analysis With Existing Te...mentioning
confidence: 75%
See 3 more Smart Citations
“…This accuracy is improved due to use of BFO process, which assists in identification of high-density feature sets, that have lower redundancies. Similarly, the precision levels for crop disease identification can be observed from table 3 MNet [8] SPED CNN [6] As per this extensive evaluation and its visualization in figure 4, it can be observed that the proposed model is able to improve classification precision levels by 18.3% when compared in SPED CNN [6], 9.4% when compared with MNet [8], and 8.5% when compared with FR CNN [9], which makes it highly useful for an extensive set of consistencyaware classification scenarios. This precision is improved due to use of ensemble classification process, which assists in identification of optimal classes for different disease types.…”
Section: Results Evaluation and Comparative Analysis With Existing Te...mentioning
confidence: 75%
“…As per this extensive evaluation and its visualization in figure 3, it can be observed that the proposed model is able to improve classification accuracy levels by 16.5% when compared in SPED CNN [6], 5.9% when compared with MNet [8], and 4.1% when compared with FR CNN [9], which makes it highly useful for a wide variety of classification scenarios. This accuracy is improved due to use of BFO process, which assists in identification of high-density feature sets, that have lower redundancies.…”
Section: Results Evaluation and Comparative Analysis With Existing Te...mentioning
confidence: 79%
See 2 more Smart Citations
“…Elfatimi et al [61] presented a method to classify beans leaf disease. The model was trained using MobileNetV2 architecture under some controlled conditions as MobileNet.…”
Section: Related Workmentioning
confidence: 99%